Approaches for the discovery of metallo‐β‐lactamase inhibitors: A review. (15th May 2019) - Shi, Cheng; Chen, Jiaxing; Kang, Xinyue; Shen, Xutong; Lao, Xingzhen; Zheng, Heng
Abstract: After more than 80 years of development, β‐lactam drugs have become the most widely used high‐efficiency, low‐toxic broad‐spectrum antibacterial drugs. However, with the widespread use and even abuse of those drugs, the resistance of major pathogens to β‐lactam drugs has increased over years, which has become a thorny problem to the public health. A common mechanism of the resistance to β‐lactams is the producing of β‐lactamases, which can hydrolyze the β‐lactam ring and inactivate these drugs. Metallo‐β‐lactamases (MBLs) are one kind of β‐lactamases that require metal ions for their catalytic activities. Although it is a well‐known strategy to recover the efficacy of β‐lactams by the combination of β‐lactamase inhibitors, there are still no MBL inhibitors that can be used in clinical practice. Therefore, it is urgent to develop MBL inhibitors. This review outlines the currently discovered MBL inhibitors with an emphasis on various strategies and approaches taken to discover MBL inhibitors, which may lead to diverse classes of inhibitors. Recent progress, particularly new screening methods, and the rational design of potent MBL inhibitors are discussed. Abstract : This review outlines the currently discovered metallo β‐lactamase inhibitors with an emphasis on various strategies and approaches taken to discover MBL inhibitors, which may lead to diverse classes of inhibitors. Recent progress, particularly new screening methods and the rational design of potent MBL inhibitors is discussed.